Severe asthma and eligibility for biologics in a Brazilian cohort. (3rd July 2021) - Marques Mello, Luane; Viana, Karynna P.; Moraes dos Santos, Felipe; Saturnino, Luciana T. M.; Kormann, Michelle L.; Lazaridis, Evelyn; Torreão, Cinthia D.; Soares, Claudia R.; Abreu, Gabriela A.; Lima, Valmar Bião de; Pinheiro, Gabriela P.; Lima-Matos, Aline; et al.
Abstract: Objective: This study aims to describe the eligibility for biologic therapies for severe asthma (SA) in a cohort of patients attending the Program for Control of Asthma (ProAR) in Bahia, Brazil. Methods: Data from SA patients (≥18 years old) attending the ProAR, that were included in a case-control study conducted from 2013 to 2015, were used to reassess patients according to a modified ERS/ATS 2014 SA criteria. Patients were then classified according to the eligibility for SA biological therapy based on current prescription labels. Results: From 544 patients in the cohort, 531 (97.6%) were included and 172 (32.4%) were identified as SA patients according to the ERS/ATS 2014 modified criteria. Of these 172 patients, 69 (40.1%) were ineligible for any of the biologicals approved for asthma (omalizumab, mepolizumab, reslizumab and benralizumab), 60 (34.9%) patients were eligible for one of the biological therapies, and 10 (5.8%) patients were eligible for all biological therapies. Conclusions: More than half of patients with SA were eligible for biologic therapy in our study, but none of them received this form of treatment. Almost half of them were not eligible to any of the approved biologics, however. The variability and overlap in patients' eligibility highlight the importance of evaluating each patient individually for a more personalized treatment approach. While there is a need to increase access for some of those eligible that may really need a biologic treatment, continuous efforts are required to develop alternatives to those who are not eligible.